The Role Of The National Sharia Council Fatwa In The Development Of The Sharia Financial Industry In Indonesia - Amanda Pramudita; Silvani Febrian; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
Study This aiming For analyze the role of the National Sharia Council (DSN) fatwa in development industry Islamic finance in Indonesia. With use approach descriptive-qualitative , research This to study DSN's contribution in aspect regulation , supervision and innovation product Islamic finance . Data obtained through studies bibliography that includes study regarding the DSN fatwa, literature academic , and regulatory government related Islamic finance . Research results show that the DSN fatwa plays a role strategic in give runway laws and guidelines operational for institution Islamic finance , so that support sustainability and legitimacy industry This . The DSN fatwa also encourages innovation product Sharia compliant finance with need society and sharia principles . Although Thus , the challenge like difference fatwa interpretation and limitations literacy public Still need attention more carry on For increase effectiveness implementation of the DSN fatwa in Indonesia .